Strategi Mitigasi Badan Penanggulangan Bencana Daerah Dalam Penanggulangan Cuaca Ekstrem di Kabupaten Bintan Tahun 2024 - Tito Raman Dhanni; Rudi Subiyakto; Ardi Putra (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Extreme weather events in Bintan Regency increased from 34 incidents in 2023 to 45 incidents in 2024, marked by strong winds and heavy rainfall, which caused damage to residential homes and disrupted community activities. This study aims to determine the mitigation strategies of the Regional Disaster Management Agency (BPBD) of Bintan Regency. This research uses a descriptive method with a qualitative approach. The study is based on Fred R. David’s theory (2016). The results of this study show that the Strategy Formulation has been fully implemented in formulating the vision and mission of BPBD Bintan regarding disaster mitigation. However, the identification of internal and external environments has not been optimal due to issues such as the wide geographical coverage of Bintan Regency and the lack of transportation facilities. The Strategy Implementation indicates that the execution by BPBD Bintan is not yet fully optimal, as some community members have not received the planned activities. The Strategy Evaluation shows that BPBD Bintan's performance has been optimal, as evidenced by the Government Institution Performance Report (LAKIP), which states that the agency has achieved 100% of its service targets for those who received services. However, field findings reveal that community understanding and preparedness are still lacking due to the absence of outreach and training programs, which are hindered by factors such as the unestablished Disaster-Resilient Villages (Destana/Katana). Nevertheless, the community perceives BPBD Bintan’s response in providing aid during disasters as satisfactory.